Genetic diversity of cucumber (Cucumis sativus) accessions differing in quantitative traits and microsatellite markers - KUMAR, RAHUL; MUNSHI, A D; BEHERA, T K; JAT, G S; CHOUDHARY, H; SINGH, MAMTA; TALUKDAR, AKSHAY (The Indian Journal of Agricultural Sciences, 2020)
The genetic diversity among 78 cucumber (Cucumis sativus L.) accessions was analyzed using 8 morphological traits and 60 SSR markers under two environmental (open field and protected cultivation) conditions. D2 analysis had grouped the 78 accessions in five major clusters. Cluster I comprised 51 accessions followed by 14, 5, 7 and 1 in cluster II, III, IV, and V respectively. The variation was observed for morphological characters like days to first female flower anthesis (37.53-58.64), days to first fruit harvest (47.28-67.43), fruit length (9.47-26.84 cm), average fruit weight (67.46-417.56 g) and vine length (96.23-170.13 cm). The first four principal components explained 87.72% of the total variation. A total of 171 alleles were amplified with a mean of 2.85 alleles per locus. The polymorphism information content (PIC) varied from 0.05 (UW084478) to 0.59 (UW084186) with a mean value of 0.36. The major allele frequency, gene diversity, and heterozygosity of these SSR markers were 0.36-0.97, 0.05-0.67 and 0.00-0.68, respectively. The dendrogram based on SSR marker analysis classified the 78 genotypes into two major groups those were subdivided into ten subgroups. Collectively, the information obtained will provide a valuable resource for germplasm conservation, genetic analyses and gene discovery in cucumber breeding.